Evaluation of antimicrobial efficacy of phosphanecopper (I) benzoylthiourea series on gram-negative bacteria isolated from feline urinary tract infection - Saifuddin Rabbani Adam Shah (2023)
Urinary tract infections (UTIs) are a common ailment in feline patients, often caused by Gram-negative bacteria. The emergence of antimicrobial resistance (AMR) bacteria in feline populations associated with UTIs has been a growing concern worldwide. Thus, development of alternative treatments is crucial to overcome this problem caused by multi drug resistant (MDR) bacteria. Hence, this study was conducted to determine the antimicrobial efficacy of Phosphanecopper (I) Benzoylthiourea Series compound on gram-negative bacteria isolated from feline urinary tract infections (UTIs) comprising Escherichia coli (E. coli), Pseudomonas aeruginosa (P. aeruginosa), and Klebsiella pneumoniae (K. pneumoniae). Three archived gram-negative bacteria were retrieved from Veterinary Bacteriology Laboratory, University Putra Malaysia and kept at room temperature and subcultured on nutrient agar prior to antimicrobial susceptibility test (AST) using Kirby-Bauer disk diffusion method and agar well diffusion method on Muller-Hinton (MH) agar plates along with minimum inhibitory concentration (MIC) using broth dilution method and minimum bactericidal concentration (MBC) on MH agar plates. Selected compounds from Phosphanecopper (I) Benzoylthiourea Series were tested on the archived clinical isolates with different concentrations such as Cu(I)ITri (3.125μM, 1.56μM, 0.78μM, 0.39μM), Cu(I)ITriDie (3.125μM, 1.56μM, 0.78μM, 0.39μM), Cu(I)ITriSar (6.25μM, 3.125μM, 1.56μM, 0.78μM) and Cu(I)ITriGly (25μM, 12.5μM, 6.25μM, 3.125μM). The findings of this study revealed that no distinct zone of inhibition can be observed using the disk diffusion and agar well diffusion methods, antimicrobial sensitivity testing (AST) indicated that the three clinical isolates were not susceptible to any of the selected compounds at varied concentrations. Moreover, results of MIC and MBC also showed that all the archived clinical isolates were not susceptible to all the selected compounds due to no clear well can be observed and the result for MBC is too numerous to count (TNTC). However, results of MIC showed slight difference in optical density (OD) reading at 600 nm wavelength (TECAN Sunrise) for the first wells with concentration of 1.56μM (Cu(I)ITri), 1.56μM (Cu(I)ITriDie), 3.125μM (Cu(I)ITriSar) and 12.5μM (Cu(I)ITriGly) against E. coli, P. aeruginosa and K. pneumoniae. Therefore, the copper complexes do not have significant antimicrobial activity against archived clinical isolates and further research is warranted potentially involving higher concentration with additional tests.
Project paper (D.V.M) - Universiti Putra Malaysia, 2023.